An economic analysis of the empty nest syndrome: What the leaving child does matters - Alan T. Piper (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This study is an empirical investigation of the empty nest syndrome, commonly understood as a situation where there are feelings of loss or loneliness for mothers and/or fathers following the departure of the last child from the family home. This investigation makes use of rich, longitudinal, nationally representative German data to assess whether there is evidence for such a syndrome. Furthermore, the analysis considers the role of two key economic variables: consumption and leisure via the standard economic concept of utility maximisation. The analysis highlights a conflict between what economic theory predicts - more disposable income and a gain of leisure time - and the psychological (and cultural) notion of the lonely, sad empty nester. This conflict is an empirical question and here it is resolved via an assessment of the change in life satisfaction that is reported when parents become empty nesters. Importantly, this investigation also tracks what the last child leaving the household goes on to do: The found reduced life satisfaction seems to be wholly moderated if the last child leaves the nest for the purposes of education, but not if for purposes of employment.
Keywords: D64; I31; 330; Life Satisfaction; Subjective Well-being; Empty Nest Syndrome; Family; Income; Consumption; Leisure